Hand orientation in hand paddle swimming - Gourgoulis, V.; Aggeloussis, N.; Vezos, N.; Antoniou, P.; Mavromatis, G. (International Journal of Sports Medicine, 2008)
The aim of this research was to study the effect of hand paddles on the pitch, the sweepback angles and other stroke kinematic characteristics of the hand during front crawl swimming. Ten female competitive swimmers swam without and with small (116 cm2) and large (268 cm2) paddles. Four cameras (60 Hz) were used to record the underwater strokes and the digitizing was undertaken using the Ariel Performance Analysis System. When the size of the paddles increased, the stroke length, the mean swimming velocity and the total duration of the stroke were significantly increased (p < 0.05), while the average velocity of the hand during the pull and the push phases were significantly decreased (p < 0.05). The stroke rate was decreased significantly (p < 0.05) only when using large paddles. The relative duration of the separate phases of the stroke, the magnitude of the medial-lateral displacements and the pitch and sweepback angles of the hand were not modified, indicating that the use of hand paddles did not caused significant alterations in the orientation and the movement of the hand during the underwater stroke in front crawl swimming.